Cryopreservation Biotechnology in Biomedical and Biological Sciences - Bozkurt, Yusuf (IntechOpen, 2018)
Cryopreservation has many biotechnological applications in different fields. This has led to an increase in importance of cryobiology as a science that examines the effect of ultra-low temperatures on cells, tissues, organs and organisms and also the freezability of these structures, while maintaining their viability. Nowadays it is well known that this form of biotechnology can be used to solve a lot of problems such as human infertility, life threatening diseases, preservation of gametes and DNA and also biodiversity conservation. Cryopreservation Biotechnology in Biomedical and Biological Sciences describes principles and application of cryopreservation biotechnology in different research areas and includes seven chapters that have been written by experts in their research fields. The chapters included in this book are thought to improve the current understanding of the different areas of using cryopreservation biotechnology.